Hello there.
Explanation:
↓↓↓↓↓↓↓↓↓↓
[tex]4-(2x-3)=3[/tex]
First, subtract by 4 from both sides.
[tex]4-(2x-3)-4=3-4[/tex]
Second, simplify.
[tex]-(2x-3)=-1[/tex]
Third, divide by -1 from both sides.
[tex]\frac{-(2x-3)}{-1}=\frac{-1}{-1}[/tex]
Fourth, simplify.
[tex]2x-3=1[/tex]
Next, add by 3 from both sides.
[tex]2x-3+3=1+3[/tex]
Then simplify.
[tex]2x=4[/tex]
Therefore, divide by 2 from both sides.
[tex]\frac{2x}{2}=\frac{4}{2}[/tex]
Finally, simplify.
[tex]x=2[/tex]
Answer⇒⇒⇒⇒x=2
Hope this helps!
Thank you for posting your question at here on Brainly.
-Charlie